Ecossocialismo: a gênese de uma ecologia social em assentamentos de reforma agrária a partir dos movimentos sociais do campo - Medeiros, João Paulo do Vale de (2013)
The world`s ecology crisis has in the capitalism way of production one of the possible causes. The unstopped search for the profits, into unlimited exploration of limited resources, made a huge transformation in human relationships with the nature, causing environment devastation, shortage of resources and species disappearance. Arises the necessity of question the society model that we are and which brings this crisis state, while we are impelled to search an alternative way. The ecosociallist praxis blows marxist principles with ecological matters, bringing important contributions regarding alternatives to capital/exploratory modus, advocating for a social fair society and environmentally sustainable. This way, by bibliographic review, we will research about this theory which have been growing in academic middles. In the same way, we will analyze the rural social movements paper in the construct of this reality. Throut the half estruture interviwes, bibliografic research and visities in the space of settlement called Moacir Lucena, that is today a exemple of rural resignification